Chronic granulomatous disease associated with Duchenne muscular dystrophy caused by Xp21.1 contiguous gene deletion syndrome: Case report and literature review - Bi, Shaohua; Dai, Liying; Jiang, Liangliang; Wang, Lili; Teng, Mia; Liu, Guanghui; Teng, Ru-Jeng (Frontiers in Genetics, 2023)
Chronic granulomatous disease (GCD) and Duchenne muscular dystrophy (DMD) are X-linked recessive disorders with their genes 4.47Mb apart within Xp21.1. A combination of both diseases is scarce and belongs to the Xp21.1 “contiguous gene deletion syndrome.” Only three cases of such a combination had been reported in the literature. We describe a male neonate who presented with sepsis at 19 days of life. Laboratory workup confirmed the diagnosis of GCD with the copy number variation sequencing (CNV-seq) revealed a 7.5Mb deletion of Xp21.2-Xp11.4 of the proband and his mother. Six known genes are involved in the deletion, including glycerol kinase (gk), dystrophin (dmd), cilia- and flagella-associated protein 47 (cfap47), gp91 (cybb), Kell antigen (xk), and retinitis pigmentosa GTPase regulator (rpgr). Laboratory studies revealed increased creatine kinase (CK) level, decreased gp91, and a positive nitroblue tetrazolium test. Due to the extensive gene deletion and the grim prognosis, the family determined to pursue conservative management. The patient passed away with a fulminant infection at the age of three-month at a local medical facility. This case, to our knowledge, is the most extensive deletion of the Xp21.1 contiguous gene deletion syndrome. A literature review of similar cases will also be presented.